Android-Based Management Information System at Bandar Lampung Technology High School - Ais Nurbanati; Sowiyah Sowiyah; Riswanti Rini; Hasan Hariri (9 772338317006)
Abstract: ANDROID BASED MANAGEMENT INFORMATION SYSTEM AT INDUSTRIAL TECHNOLOGY MIDDLE SCHOOL IN BANDAR LAMPUNG. This study aimed to analyze and describe an Android-based SIM at SMK SMTI (Industrial Technology High School). There are four elements described, namely (1) planning an Android-based SIM at SMK SMTI Bandar Lampung, (2) organizing an Android-based SIM at SMK SMTI Bandar Lampung, (3) implementing an Android-based SIM at SMK SMTI Bandar Lampung, and (4) monitoring and evaluation of an Android-based SIM at SMK SMTI Bandar Lampung. The approach used in this study was a descriptive qualitative approach. The research data were obtained from two sources, namely researchers and 10 informants. Data collection techniques were carried out by: (1) interviews, (2) observation, and (3) document study. The validity of the data was obtained from the findings that were carried out by testing the credibility, dependability and confirmability. The results showed that, (1) the SIM planning at SMK SMTI Bandar Lampung accommodated the needs of steakholders obtained through brainstorming and selecting them according to school objectives. (2) SIM organization at SMK SMTI Bandar Lampung socialized Android-based SIM according to users such as teachers, students and parents. (3) the implementation of an Android-based SIM at SMK SMTI Bandar Lampung could improve education quality services that are effective and efficient. (4) monitoring and evaluation of SIM-based SMK SMTI Bandar Lampung could be done by looking through the admin account how active teachers, students and parents were using SIM for teaching and learning activities. Keywords: SIM, Manajemen, Android DOI: 10.23960/jmmp .v9.i1.202103